Neural Substrates of the Drift-Diffusion Model in Brain Disorders - Gupta, Ankur; Bansal, Rohini; Alashwal, Hany; Kacar, Anil Safak; Balci, Fuat; Moustafa, Ahmed A. (Frontiers in Computational Neuroscience, 2022)
Many studies on the drift-diffusion model (DDM) explain decision-making based on a unified analysis of both accuracy and response times. This review provides an in-depth account of the recent advances in DDM research that which ground different DDM parameters on several brain areas, including the cortical cortex and basal ganglia areas. Furthermore, we discuss the changes in DDM parameters due to structural and functional impairments in several clinical disorders, including Parkinson’s disease, Attention Deficit Hyperactivity Disorder (ADHD), Autism Spectrum Disorders, Obsessive-Compulsive Disorder (OCD), and schizophrenia. Our frameworkThis review thus uses DDM to provide a theoretical understanding of different brain disorders.